Speaker-independent Malay vowel recognition of children using multi-layer perceptron - Hua, Nong Ting; Yunus, Jasmy (IEEE, 2004)
Most of the speech recognitions are based on adult speech sounds. Less research is done in the recognition of children speech sounds. The speech of children is more dynamic and inconsistent if compared to adults speech. This paper investigates the use of neural networks in recognizing 6 Malay vowels of Malay children in a speaker-independent manner. Multi-layer Perceptron with one hidden layer was used to recognize these vowels. The Multi-layer Perceptron was trained and tested with speech samples of Malay children with their ages between seven and ten years old. A single frame of cepstral coefficients were extracted around the vowel onset point using Linear Predictive Coding. The vowel length was examined from 5 ms to 70 ms. Experiments were conducted to determine the optimal vowel length as well as the number of cepstral coefficients.